The Boundary Layer Flow, Heat and Mass Transfer beyond an Exponentially Stretching/Shrinking Inclined Sheet - Mohd Azmi, Hazirah; Mohamed Isa, Siti Suzilliana Putri; Md. Arifin, Norihan (CFD Letters, 2021)
The characteristics of heat and mass transmission, together with the features of fluid flow where the fluid is bounded by a stretching/shrinking sheet are influenced by the rotation angle of the sheet. In addition, the comparison between two conditions of stretching/shrinking sheet, known as: 1. normal position of sheet (zero rotation), 2. when it is inclined, contribute significant applications in science and technology, especially in experimental and theoretical research. According to this fact, this paper examines the impact of stretching and shrinking parameters acting on the inclined sheet, which contribute to the changes on the flow, heat and mass transfer in a Newtonian fluid. The variations of velocity, temperature and concentration of Newtonian fluid also being observed. The momentum, energy and concentration equations are acting as the controlling equations and written as partial differential equations (PDE). Subsequently, these equations were transformed into the ordinary differential equations (ODE) by using the similarity transformation. Finally, the ODE is solved numerically by bvp4c program in Matlab software. Dual numerical solutions are obtained in this paper, and presented in the figure form. The features of flow pattern, heat and mass transfer are described in details, together with the profiles of velocity, temperature and concentration of the related fluid. As a result, it is found that rate of skin friction coefficient, local Nusselt number, and local Sherwood number are reduced with the addition of inclination angle. On the other hand, velocity profile and the local Nusselt number are enhanced due to the impact of stretching rate at the inclined sheet.